2020
DOI: 10.1016/j.mayocpiqo.2019.10.002
|View full text |Cite
|
Sign up to set email alerts
|

A Process of Acceptance of Patient Photographs in Electronic Medical Records to Confirm Patient Identification

Abstract: Appropriate patient identification is a critical component of safe health care delivery. With increasing reliance on electronic medical records (EMRs), errors of test ordering and documentation have become commonplace. Incorporating patients' photograph in the EMR has considerably decreased error frequency and improved health care delivery by making it easier for physicians to identify a patient. We conducted a survey of all 35 physicians working in the Executive Health Program to determine the importance of h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
6
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 6 publications
0
6
0
Order By: Relevance
“…This theme included cases involving key EHR features or functionality that developers are responsible for creating: Feature/function not working as designed, eg, a user noted that “there's a way to download the patient's pharmacy history from any pharmacy here, and that sometimes doesn't work so well, but I think that's a computer glitch.” Feature/function not working as desired by users, eg, one physician commenting about the medication reconciliation procedure noted that “They [EHR designers/developers] did not highlight which meds had been changed, but I think it was a conscious decision they made that I just don't agree with.” User versus vendor expectations of how specific functionality would be used, eg, When asked about including patient pictures in their EHR, a local physician commented “Well, it would be great if I could take photos with my phone and you know, send them through and get them in the patient's chart.’ And we [local IT folks] were just kind of like, ‘Hmm, no.’” Although a seemingly great idea, it was never considered by the EHR designers who only anticipated that registration clerks would need to upload patient photos 11 Interactions with other systems, eg, one organization had trouble getting their new EHR to work with their existing pharmacy management system 12 .…”
Section: Resultsmentioning
confidence: 99%
“…This theme included cases involving key EHR features or functionality that developers are responsible for creating: Feature/function not working as designed, eg, a user noted that “there's a way to download the patient's pharmacy history from any pharmacy here, and that sometimes doesn't work so well, but I think that's a computer glitch.” Feature/function not working as desired by users, eg, one physician commenting about the medication reconciliation procedure noted that “They [EHR designers/developers] did not highlight which meds had been changed, but I think it was a conscious decision they made that I just don't agree with.” User versus vendor expectations of how specific functionality would be used, eg, When asked about including patient pictures in their EHR, a local physician commented “Well, it would be great if I could take photos with my phone and you know, send them through and get them in the patient's chart.’ And we [local IT folks] were just kind of like, ‘Hmm, no.’” Although a seemingly great idea, it was never considered by the EHR designers who only anticipated that registration clerks would need to upload patient photos 11 Interactions with other systems, eg, one organization had trouble getting their new EHR to work with their existing pharmacy management system 12 .…”
Section: Resultsmentioning
confidence: 99%
“…These findings are consistent with prior research of patients' acceptance of photographs for patient identification in pediatrics 7 and acceptance of clinical photographs in teledermatology, radiology, general internal medicine, anesthesiology, and for use in medical education, which demonstrates that patients are generally willing to share their PHI with clinicians, even when they have concerns about privacy and information security. [12][13][14][15][16][17][22][23][24][25][26][27] For example, one study demonstrated that, although 82% of patients had concerns about the security of EHRs, 75% agreed that the benefits of EHRs outweighed the risks to security. 25 Another study revealed that patients were open and willing to share PHI with clinicians, and their comfort with sharing information increased when privacy concerns were addressed by clinicians.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have shown low rates of patient refusal for clinical photographs (e.g., photographs of skin rashes) used for patient care and medical education. [12][13][14][15][16][17] Lau et al 13 found that 98% of patients would accept having a clinical photograph in the medical record if it were used by their health care provider for medical purposes. Among patients enrolled in a pilot study in an ED, 84% had positive attitudes toward the use of clinical photographs for medical education.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Aseem et al [53] have proposed a strategy called SMART that is incorporating the patient's photograph in the electronic medical record to easily identify the patient that makes it simple for the doctor to provide health care to that patient. This strategy contains two phases.…”
Section: Related Workmentioning
confidence: 99%